Manuali, ricette, propositi e altre facce dell’animale indisciplinato - Canzonieri, Armando (Rivista Italiana di Filosofia del Linguaggio, 2013)
In this paper I try to single out some structural appearances of human culture. I argue that cultural life is characterized from the presence of intentions and that to internalize intention means to create a injury in our consciousness. I identify in manuals the cultural object that human beings use to organize this injury. Then I try to argue that in cultural life we can find always two different manuals: one that says how we have to comport to became human and another one that try to indicate how to run away from this cultural life so to live our human life so as it comes. When a manual try to answer to the question: how I have